Alcohol consuption among academics of physical education - Costa Júnior, João Jorge da; Gomes, Rita Ivana Barbosa; Sousa, Vanessa Emille Carvalho de; Sardinha, Ana Hélia de Lima; Viveiros, Maria Teresa Martins (Rev Rene, 2012)
This is a cross-sectional study that aims to determine the prevalence of alcohol consumption among physical education students of a public university of São Luís-MA. The sample consisted of 80 students. It was identified the following profile: 44 men and 36 women, aged between 18 and 21 years, most Catholics and having family income between $ 1,440.00 and $ 2,400.00. The prevalence of alcohol use was 95%, being higher among men (97.72%). The problematic use of alcohol, detected by the CAGE test, showed that 15% had physical and psychic problems and 23.75% mentioned to have missed classes in the last 30 days because of alcohol consumption. The study showed a significant number of students that had an exacerbated level of alcohol consumption, which draws attention to the need of addressing the topic of alcoholism in the academic scenario.